When leaders fill the room: the effect of authentic leadership on employees’ performance and the role of affective commitment - Ribeiro, Neuza (2020)
Purpose – One of CSR’s main concern relates to the way an organization is able to develop Social Responsibility orientations guided towards its internal publics. How leaders behave in working contexts may decisively influence CSR’s social performance of an organization. This study seeks to understand how (a) Authentic Leadership (AL) influences employees' Affective Commitment (AC), (b) AL influences Individual Performance (IP), (c) AC influences IP and (d) AC mediates the relationship between AL and IP. Design/methodology/approach – The sample included 212 Portuguese employees from small and medium sized companies. A quantitative methodology was used following Baron and Kenny’s linear regression method and Sobel test to examine the existence of the proposed mediational relationship. Findings - The results show that AL explains employees’ AC and their IP. Moreover, AC mediates the relationship between AL and employees’ IP. Thus, leaders’ authenticity promotes employees’ affective bond to their organization, which in turn, increases their individual performance. Practical implications - This research has practical implications for CSR’s internal policies on social performance, with high contribute for socially responsible human resources management practices, particularly in what regards the way an organization should develop social internal policies supporting CSR implementation. Results also provide reasoning for CSR practices directed towards increasing employee commitment through augmenting AL. Originality/value – This study enriches the knowledge about the relevance of emerging area such as AL theory, CSR internal policies and responds to the need to understand underlying mechanisms linking leaders’ authenticity with workers’ commitment and performance (i.e., testing the construct’s nomological network).